2000
DOI: 10.1152/ajpgi.2000.278.4.g625
|View full text |Cite
|
Sign up to set email alerts
|

Mode of action of ANG II on ion transport in guinea pig distal colon

Abstract: The effect of ANG II on mucosal ion transport and localization of ANG type 1 receptor (AT(1)R) in the guinea pig distal colon was investigated. Submucosal/mucosal segments were mounted in Ussing flux chambers, and short-circuit current (I(sc)) was measured as an index of ion transport. Serosal addition of ANG II produced a concentration-dependent (10(-9)-10(-5) M) increase in I(sc). The maximal response was observed at 10(-6) M; the increase in I(sc) was 164.4 +/- 11.8 microA/cm(2). The ANG II (10(-6) M)-evoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 40 publications
2
17
1
Order By: Relevance
“…Our present results showed that Ang II-stimulated O 2 Ϫ ⅐ generation was observed only in cardiovascular tissues but not in colon, although previous studies have demonstrated the presence and the functions of AT1 and AT2 receptors in colon. 19 Our results have also shown that Ang II selectively stimulated cardiac COX-2 but not COX-1 enzyme expression in vivo. Similar result was also reported by Young et al 10 on cultured SMCs.…”
Section: Discussionsupporting
confidence: 64%
“…Our present results showed that Ang II-stimulated O 2 Ϫ ⅐ generation was observed only in cardiovascular tissues but not in colon, although previous studies have demonstrated the presence and the functions of AT1 and AT2 receptors in colon. 19 Our results have also shown that Ang II selectively stimulated cardiac COX-2 but not COX-1 enzyme expression in vivo. Similar result was also reported by Young et al 10 on cultured SMCs.…”
Section: Discussionsupporting
confidence: 64%
“…This is in contrast with angiotensin II-and substance P-evoked Cl Ϫ secretory response, which involves submucosal cholinergic neurons (13,21). Therefore, baicalein may act directly on epithelial or subepithelial cells in the mucosa to evoke Cl Ϫ secretion, which involves PG synthesis.…”
Section: Discussionmentioning
confidence: 96%
“…Secretagogue-induced Cl Ϫ secretion by the GI tract is important because Cl Ϫ secretion provides an essential driving force for the lubrication of intestinal contents during regular bowl movements or the flushing of microbial organisms or artificial irritants in host defense responses [2,3]. Epithelial Cl Ϫ channels, especially the cAMP-activated Cl Ϫ channels, play an important role in regulating and maintaining the normal physiological functions of the GI tract.…”
Section: Bak Foong Pills (Bfp Also Known As Bai Feng Wan)mentioning
confidence: 99%
“…Z980035) that has long been used for treating gynecological disorders and improving of overall body functions, including gastrointestinal (GI) function [1]. However, the cellular signaling mechanism underlying BFP action, especially on the GI tract, has not been elucidated.Secretagogue-induced Cl Ϫ secretion by the GI tract is important because Cl Ϫ secretion provides an essential driving force for the lubrication of intestinal contents during regular bowl movements or the flushing of microbial organisms or artificial irritants in host defense responses [2,3]. Epithelial Cl Ϫ channels, especially the cAMP-activated Cl Ϫ channels, play an important role in regulating and maintaining the normal physiological functions of the GI tract.…”
mentioning
confidence: 99%